2010
DOI: 10.1021/jf103904b
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Potential of Three Triterpenic Acids in Human Liver Cancer Cells

Abstract: Three triterpenic acids, oleanolic acid, ursolic acid and maslinic acid, at 2 or 4 μmol/L were used to study their antiangiogenic potential in human liver cancer Hep3B, Huh7 and HA22T cell lines. The effects of these compounds upon the level and/or expression of hypoxia-inducible factor (HIF)-1α, basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), interleukin (IL)-8, urokinase plasminogen activator (uPA), reactive oxygen species (ROS), nitric oxide (NO) and cell invasion and migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…Interestingly, it has been recently shown that ursolic acid enriched in NFJ and also in many other plant products suppresses endogenous mRNA expression of multiple pro-angiogenic genes, including HIF-1α, in human liver cancer cells (28), thereby suggesting its antiangiogenic potential. Though not assessed herein, it is suggested that among the constituents of noni juice, ursolic acid may be a key compound associated with the NFJ's repressive effect on the manganese-induced HIF-1α protein expression in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been recently shown that ursolic acid enriched in NFJ and also in many other plant products suppresses endogenous mRNA expression of multiple pro-angiogenic genes, including HIF-1α, in human liver cancer cells (28), thereby suggesting its antiangiogenic potential. Though not assessed herein, it is suggested that among the constituents of noni juice, ursolic acid may be a key compound associated with the NFJ's repressive effect on the manganese-induced HIF-1α protein expression in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos et al (2008) found that UA prevented DNA damage via increase of DNA repair and anti-proliferative properties in HepG2 cells. Lin et al (2011) found that UA reversed the invasion and migration of Hep3B and Huh7 cell lines at 4 lmol/ L. Son et al (2013) reported that UA blocked HepG2 cellular metabolism via AMPK activation and GSK3b phosphorylation, and thus induced apoptosis of HepG2 cells. On the suppression of carcinogenic side, UA could prevent HCC from nonalcoholic fatty liver disease (NAFLD), insulin resistance, inflammation and oxidation stress.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al used UA to treat human liver cancer (i.e., Hep3B, Huh7, and HA22T cells) cell lines, and found that the expressions of HIF-1, VEGF, and IL-8 significantly reduced in a dose-dependent manner. Additionally, cell invasion and migration were also found to have declined along with the suppressed expression of uPA [46]. In vitro and in vivo studies by Kanjoormana et al revealed the anti-angiogenic characteristics of UA: UA inhibited capillary formation of the tumor induced by highly metastatic melanoma (B16F-10) cells in C57BL/6 mice.…”
Section: Anti-angiogenesismentioning
confidence: 99%